Imigração coreana e protestantismo no Brasil: diálogo entre identidade religiosa e identidade étnica - Silva, Silvania Maria Portela (2009)
In São Paulo city, the Korean population is nearly 40 thousand people, being considered the largest concentration of this human group in Brazil. This immigration happened in a very concentrated way, in a time interval smaller than 50 years, between the sixties and current days. A very peculiar characteristic of this phenomenon was the quick economical growth. Another is the considerable number of Protestants among the Korean community in São Paulo. In less than 50 years, Korean were able to establish around 71 protestant churches, but only one Buddhist temple (despite of the confucionist tradition of these people) and only one catholic church in Sao Paulo. These numbers present an undoubting religious heritage in the colony. This research will analyze the role of the protestant social networks in São Paulo city and their relations with the Korean immigration from the sixties and on. The dissertation analyzes whether or not (and how) the protestant social networks favored the new-comers, including the non-legal immigrants what was quite relevant in the Korean case; and also investigates the influence these networks had in the adaptation process of the immigrants to Sao Paulo city reality.